Cryopreserved human aortic root allografts arterial wall: Structural changes occurring during thawing - Novotny, Robert; Slizova, Dasa; Hlubocky, Jaroslav; Krs, Otakar; Spatenka, Jaroslav; Burkert, Jan; Fiala, Radovan; Mitas, Petr; Mericka, Pavel; Spacek, Miroslav; Hlubocka, Zuzana; Lindner, Jaroslav (PloS one, 2017)
BACKGROUND: The aim of our experimental work was to assess morphological changes of arterial wall that arise during different thawing protocols of a cryopreserved human aortic root allograft (CHARA) arterial wall. METHODS: The experiment was performed on CHARAs. Two thawing protocols were tested: 1, CHARAs were thawed at a room temperature at +23°C; 2, CHARAs were placed directly into a water bath at +37°C. MICROSCOPIC SAMPLES PREPARATION: After fixation, all samples were washed in distilled water for 5 min, and dehydrated in a graded ethanol series (70, 85, 95, and 100%) for 5 min at each level. The tissue samples were then immersed in 100% hexamethyldisilazane for 10 minutes and air dried in an exhaust hood at room temperature. Processed samples were mounted on stainless steel stubs, coated with gold. RESULTS: Thawing protocol 1: All 6 (100%) samples showed loss of the endothelium and damage to the subendothelial layers with randomly dispersed circular defects and micro-fractures without smooth muscle cells contractions in the tunica media. Thawing protocol 2: All 6 (100%) samples showed loss of endothelium from the luminal surface, longitudinal corrugations in the direction of blood flow caused by smooth muscle cells contractions in the tunica media with frequent fractures in the subendothelial layer. CONCLUSION: All the samples thawed at the room temperature showed smaller structural damage to the CHARA arterial wall with no smooth muscle cell contraction in tunica media when compared to the samples thawed in a water bath.
Keywords: kryoprezervace; aorta; Humans; Cryopreservation; lidé středního věku; Female; chirurgická náhrada chlopně; dospělí; Tissue Donors; lidé; alografty; Heart Valve Prosthesis; Transplantation, Homologous; Adult; dárci tkání; ženské pohlaví; Male; Middle Aged; Allografts; srdeční chlopně umělé; mužské pohlaví; homologní transplantace; aortální chlopeň; Aorta; Heart Valve Prosthesis Implantation; Aortic Valve